A Grid-based Filter for Tracking Bats Applying Field Strength Measurements - Hartmann, Markus; Nowak, Thorsten; Pfadenhauer, Oliver; Thielecke, Jörn; Heuberger, Albert (12th Annual Conference on Wireless On-demand Network Systems and Services (WONS), 2016)
Nowadays, many applications demand precise localization information. One of those applications is wildlife monitoring, e.g. tracking of bats. Wireless sensor networks featuring field strength measurements are a promising approach to track tiny and lightweight animals. In this paper a robust grid-based filter for the localization of bats based on field strength measurements is proposed. Therefore, fundamentals of field strength-based direction finding and optimal filtering are presented. A gridbased filtering approach to the problem of field strength-based position estimation of bats is derived and evaluated by Monte Carlo simulations.
Keywords: Gain; Direction-of-arrival estimation; Antennas; Antenna measurements; Estimation; Trajectory; Bayes methods